Carrier-envelope phase dependence of the directional fragmentation and hydrogen migration in toluene in few-cycle laser fields - Hui Li; Nora G. Kling; Benjamin Förg; Johannes Stierle; Alexander Kessel; Sergei A. Trushin; Matthias F. Kling; Spyros Kaziannis (Structural Dynamics, 2016)
The dissociative ionization of toluene initiated by a few-cycle laser pulse as a function of the carrier envelope phase (CEP) is investigated using single-shot velocity map imaging. Several ionic fragments, CH3+, H2+, and H3+, originating from multiply charged toluene ions present a CEP-dependent directional emission. The formation of H2+ and H3+ involves breaking C-H bonds and forming new bonds between the hydrogen atoms within the transient structure of the multiply charged precursor. We observe appreciable intensity-dependent CEP-offsets. The experimental data are interpreted with a mechanism that involves laser-induced coupling of vibrational states, which has been found to play a role in the CEP-control of molecular processes in hydrocarbon molecules, and appears to be of general importance for such complex molecules.